First-principles investigation of structural, electronic, mechanical, and optical properties of Tl-based halide perovskites (TlXF3; X = Ti, Zr) for reflective coating applications - Amina; Maryam Liaqat; Salhah Hamed Alrefaee; Muhammad Inam Ul Haq; Dilsora Abduvalieva; Naseem Akhter; Vineet Tirth; Ali Algahtani; Amnah Mohammed Alsuhaibani; Moamen S. Refat; N.M.A. Hadia (Electrochemistry Communications)
The pursuit of advanced materials to address global energy challenges has directed attention to halide perovskites, known for their promising technological applications. In this study, we investigate the structural, electronic, elastic, and optical properties of Tl-based fluoro-perovskites TlXF3 (X = Ti, Zr) using density functional theory (DFT) with the Wien2k package. Structural stability is confirmed via tolerance factor analysis, while thermodynamic stability is validated through negative formation energies. Phonon dispersion calculations affirm the dynamic stability of these compounds. The optimized lattice constants are found to be 4.25 and 4.47 Å. Employing the modified Becke-Johnson potential, the electronic band structure and density of states are computed revealing a half-metallic nature of both compounds, with excellent consistency between band structure and density of states findings. In both material the valence and conductions bands are overlapped at Fermi level for spin up configuration while in spin down configuration they have band gap of 4.8 eV and 5.6 eV for TlTiF3 and TlZrF3 respectively. Elastic properties show that both TlTiF3 and TlZrF3 meet mechanical stability criteria, with TlTiF3 demonstrating superior resistance to compressive and shear stresses, indicating enhanced mechanical robustness. The elastic analysis further indicates anisotropic, ductile behavior in both compounds. Optical analysis across a broad energy range highlights the potential of these materials for optoelectronic applications, suggesting their suitability for advanced device architectures. This study provides a foundation for further experimental exploration and device innovation in the field of halide perovskites.